2010
DOI: 10.1590/s1517-83822010000400029
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of biofilm production on polystyrene by Listeria, Escherichia coli and Staphylococcus aureus isolated from a poultry slaughterhouse

Abstract: This study assessed biofilm formation on polystyrene by Staphylococcus aureus, Listeria monocytogenes, L. welshimeri and Escherichia coli, isolated from a slaughtering plant, grown on tryptic soy broth (TSB) using different glucose concentrations. The tested bacteria produced biofilm in at least one of the concentrations used, and some of them were strong biofilm producers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 3 publications
6
24
0
6
Order By: Relevance
“…Bacterial study. Five collection strains and widely known biofilm producers, that is, S. aureus 15981 (77-80), S. epidermidis ATCC 35984 (81)(82)(83), E. coli ATCC 25922 (84)(85)(86), P. aeruginosa ATCC 27853 (87)(88)(89), and S. maltophilia ATCC 13637 (90,91), were used. All the strains were kept frozen at Ϫ80°C until the experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial study. Five collection strains and widely known biofilm producers, that is, S. aureus 15981 (77-80), S. epidermidis ATCC 35984 (81)(82)(83), E. coli ATCC 25922 (84)(85)(86), P. aeruginosa ATCC 27853 (87)(88)(89), and S. maltophilia ATCC 13637 (90,91), were used. All the strains were kept frozen at Ϫ80°C until the experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…These isolates were previously identified by Martins et al (2013) and Riboldi et al (2009 Quantitative determination of biofilm was determined by crystal violet assay (CV) in accordance with Stepanović et al (2007) with some modifications. This methodology was chosen, for being the reference protocol to detection of biofilm formed by isolated food pathogens (Rodrigues et al 2010, Marinho et al 2013, Pinto et al 2015. In summary, three to five colonies were suspended in 4 ml of 0.85% (w/v) NaCl solution and compared with 0. glucose was added to each well and the microplate was incubated at 37ºC for 24 h. After incubation the plate was washed with 0.85% (w/v) NaCl solution for three times to remove non-adherent cells, 200 µl of 100% methyl alcohol was added for 20 min to fix the adhered cells.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Several studies have reported high biofilm formation capacity of L. monocytogenes on polystyrene material (Rodrigues et al, 2010;Kadam et al, 2013) and thus reveal that the material is propitious to colonization by L. monocytogenes biofilms.…”
Section: Resultsmentioning
confidence: 99%